The problem statement tells us that E(x) is differentiable at x = 0 ... We wish to show E is differentiable everywhere else and on top of that E'(x) = E(x). The proof is as follows:
Let a be fixed and arbitrary, then via definition E'(a) = lim (E(a + h) - E(a)) / h , as h --> 0
But E(a + h) = E(a) E(h) according to the given property for E(x), hence the above equals
lim [E(a) E(h) - E(a)] / h =factoring out the constant E(a) in the numerator= E(a) lim [(E(h) - 1)] / h , as h --> 0 (*)
Now since E(0) = 1, the limit of (E(h) - 1) / h as h--> 0 is of the ambiguous form 0/0. So the L'Hopitale Rule applies and taking derivatives from top and buttom it tells us the aforementioned limit equals lim (E'(h) - 0) / 1 as h --> 0 which equals E'(0) / 1 = 1/1 or simply 1.
Hence the limit exists, which proves E is differentiable and besides that, from (*) we conclude that E'(a) = E(a) times 1 = E(a). Since the latter is true for every a in the domain, it follows that E'(x) = E(x) for all x.
The example of course is Exp(x) or any exponential function with base b > 1 or 0 < b < 1. I believe there is a rather deep theorem stating that any continuous function f(x) satisfying the given functional equation with f(0) = 1 must be an exponential function. The result is due to Euler if I recall correctly.
****
I just saw the comment below by the other contributor. We do know the limit of E(h) as h --> 0: E'(0) exists so E is differentiable at x = 0 which means E is continuous at zero. Hence lim E(h) = E(0) = 1 as h --> 0, according to the definition of continuity; the two-sided limit of the function equals the value of the function at that point.